German religious women in late Ottoman Beirut: competing missions - Hauser, Julia (Studies in Christian mission, 2015)
Origins and implications of a mission -- Long-distance empathy and denominational competition -- Struggling with the self -- Communicating in the language of love -- Educating orphans -- Catering to a diverse clientele -- Veteran deaconesses and their ways of accommodation -- Sowing the home field